Entre a colonização do noroeste do Paraná e a preservação da memória de um povo esquecido : os Xetá - Rebecchi, Murilo (2014)
This paper analyzes the process of occupation by the colonizing companies in the Northwest of Paraná, and this interest led occupation and the relationships we have established this process in the second half of the twentieth century. We discuss in this paper as the basis the fallacy of traditional historiography around the depopulation of this territory when the arrival of settlers, who speaks especially for long tried to deny the existence of Xetá people. These people occupied these lands long before the arrival of modern settlers, but many factors still ended up being almost extinct during the 1950s and 1960s Thus, our goal in this work is to identify how it was built and has been representative memory Xetá people in some of the municipalities which currently are located in the territory formerly occupied by this people. We seek to identify places that we classify as places of memory to Xetá and work towards elucidating the representations that people who experience / frequent these spaces have the Xetá. In addition we also seek to identify public policies to preserve these spaces in cities that have them.